2016
DOI: 10.1111/jan.12890
|View full text |Cite
|
Sign up to set email alerts
|

Integrative review: postcraniotomy pain in the brain tumour patient

Abstract: Aim To conduct an integrative review to examine evidence of pain and associated symptoms in adult (≥ 21 years of age), post-craniotomy, brain tumor patients hospitalized on intensive care units. Background Healthcare providers believe craniotomies are less painful than other surgical procedures. Understanding how post-craniotomy pain unfolds over time will help inform patient care and aid in future research and policy development. Design Systematic literature search to identify relevant literature. Informa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 59 publications
0
12
0
1
Order By: Relevance
“…Neurosurgical procedures cause more pain than anesthesiologists expect, 4 and post-craniotomy pain is not always well understood. 5 However, clinicians have become more aware of the incidence and intensity of post-craniotomy pain. There is a large variation in the occurrence of postoperative pain and the requirement of analgesic medication in neurosurgical patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neurosurgical procedures cause more pain than anesthesiologists expect, 4 and post-craniotomy pain is not always well understood. 5 However, clinicians have become more aware of the incidence and intensity of post-craniotomy pain. There is a large variation in the occurrence of postoperative pain and the requirement of analgesic medication in neurosurgical patients.…”
Section: Introductionmentioning
confidence: 99%
“… 6 , 7 In a recent review of 26 studies assessing different aspects of postcraniotomy pain, 15 studies reported pain percentages in the first two postoperative days up to 60%–96%. 5 It is unclear why this great variation of the incidence of postoperative pain exists in craniotomy patients. Attributable factors could be the perioperative opioid and analgesic regiment used, the exact moment of the first postoperative pain score and the composition of the neurosurgical population.…”
Section: Introductionmentioning
confidence: 99%
“…7 Pain after craniotomy may affect hospital stay, medication costs, quality of life and the development of persistent pain. 8 Although there have been considerable developments in drugs for postoperative sedation of pain, many drugs (Morphine, etc.) have the effect of inhibiting respiration and anesthesia, resulting in not widely used in patients after neurosurgery.…”
Section: Pain Carementioning
confidence: 99%
“…Kesamaan masalah keperawatan utama yang muncul yaitu nyeri akut. Nyeri post kraniotomi paling banyak berpengaruh di dunia dan nyeri post kraniotomi diidentifikasi sebagai prioritas kesehatan masyarakat (Guilkey et al, 2016). Masalah pernapasan menjadi perhatian utama karena komplikasi paru yang berpengaruh pada pernapasan terutama komplikasi paru pasca operasi, merupakan penyebab penting morbiditas dan mortalitas pada pasien bedah saraf (Misra, 2016).…”
Section: Metode Penelitianunclassified